Correlation of Service Quality, Social Media, Discounts on Customer Satisfaction of PLN Mobile Application with Digital Marketing as a Mediation Variable (Case Study of PLN UP3 Medan ULP Delitua) - Bunga Widuri Marina; Nurafrina Siregar; Slamet Widodo (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze the influence of service quality, social media, and discounts on customer satisfaction of PLN Mobile application users, with digital marketing as a mediating variable. In the increasingly developing digital era, good service quality, effective use of social media, and attractive discounts are considered to have an important role in increasing customer satisfaction. In addition, integrated digital marketing is a key factor in mediating the influence of these factors on customer satisfaction. This research method uses a quantitative approach by collecting data through questionnaires distributed to PLN Mobile application users in the PLN ULP Delitua work area. Data analysis was carried out using the Structural Equation Modeling (SEM) technique to test the relationship between the variables studied. The results of the study show that the quality of service, social media, and discounts have a significant influence on customer satisfaction directly. Digital marketing was found to have a strong mediating role, where digital marketing strengthened the relationship between independent variables (quality of service, social media, and discounts) and customer satisfaction. This research makes an important contribution to PLN in optimizing digital marketing strategies, improving service quality, and utilizing social media and discounts to improve the user experience of the PLN Mobile application. These findings also show that digital marketing can be an effective tool in strengthening customer loyalty and influencing their satisfaction in the context of application-based public services